The role of catecholamines in modulating responses to stress: Sex‐specific patterns, implications, and therapeutic potential for post‐traumatic stress disorder and opiate withdrawal. (20th April 2020) - Ross, Jennifer A.; Van Bockstaele, Elisabeth J.
Abstract: Emotional arousal is one of several factors that determine the strength of a memory and how efficiently it may be retrieved. The systems at play are multifaceted; on one hand, the dopaminergic mesocorticolimbic system evaluates the rewarding or reinforcing potential of a stimulus, while on the other, the noradrenergic stress response system evaluates the risk of threat, commanding attention, and engaging emotional and physical behavioral responses. Sex‐specific patterns in the anatomy and function of the arousal system suggest that sexually divergent therapeutic approaches may be advantageous for neurological disorders involving arousal, learning, and memory. From the lens of the triple network model of psychopathology, we argue that post‐traumatic stress disorder and opiate substance use disorder arise from maladaptive learning responses that are perpetuated by hyperarousal of the salience network. We present evidence that catecholamine‐modulated learning and stress‐responsive circuitry exerts substantial influence over the salience network and its dysfunction in stress‐related psychiatric disorders, and between the sexes. We discuss the therapeutic potential of targeting the endogenous cannabinoid system; a ubiquitous neuromodulator that influences learning, memory, and responsivity to stress by influencing catecholamine, excitatory, and inhibitory synaptic transmission. Relevant preclinical data in male and female rodents are integrated with clinical data in men and women in an effort to understand how ideal treatment modalities between the sexes may be different. Abstract : Posttraumatic stress disorder (PTSD) and opiate substance use disorder (SUD) arise from maladaptive learning responses that are perpetuated by hyperarousal of the salience network. Catecholamines modulate learning and stress circuits that exert substantial influence over the salience network by enhancing salience attribution to emotionally salient fear‐related, or drug‐related stimuli, in PTSD and opiate SUD, respectively. The endogenous cannabinoid system is a ubiquitous neuromodulator that influences learning, memory, and responsivity to stress by influencing catecholamine, excitatory, and inhibitory synaptic transmission. We argue that the endogenous cannabinoid system may have therapeutic potential for the treatment of PTSD and opiate SUD based on its multifaceted ability to restore salience network balance as it dampens hyperarousal of the catecholamine neurotransmitter systems.